Revolusi EDSA: Bentuk Perlawanan Rakyat Terhadap Rezim Otoriter di Filipina - Darojat, Muhammad Miftachul (Universitas Negeri Gorontalo, 2025)
The EDSA Revolution, or People Power Revolution, that took place in the Philippines in 1986 is one of the most important examples of a people’s movement that successfully overthrew an authoritarian regime without violence. The movement emerged in response to the two-decade-long dictatorship of Ferdinand Marcos. Driven by electoral fraud, socio-economic discontent, and political repression, millions of Filipinos joined the peaceful protests that ultimately ended Marcos’ rule. This paper will discuss the political, economic, and social background that sparked the revolution, the chronology of events, the role of civil society and the Catholic Church, and the long-term impact of the EDSA Revolution on the Philippines and similar movements around the world.